Networking for plant genetic resources - Maggioni, L.; Engels, J. (2014)
Since the domestication of wild plants, farmers have more or less consciously manipulated natural diversity under their specific conditions by selecting new combinations of genes and giving rise to uncounted forms and varieties of crops. Plant breeding is the scientific process that makes use of the existing genetic variation to improve yield, to direct and to speed up adaptation to ever-changing environmental conditions, including resistance or tolerance to pests and diseases, as well as to improve food quality. Agricultural production and world food security are therefore directly and strongly dependent on plant genetic diversity. Thus, this precious biological resource needs to be preserved and remain available for present and future generations.